ANALISIS ATAS PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI INDONESIA - Yanuar Irawan; Havid Sularso; Yusriati Nur Farida (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
The Research aims to examine the effect of Size of the Company (SIZE), Profitability (ROA), Leverage (DAR), Institutional Ownership (INST), and Quality of Audit (QA) to Tax Avoidance. The object under study is property and real estate companies that listed on the Indonesia Stock Exchange for the years 2013-2015. The sampling method used in this study is nonprobability sampling with purposive sampling technique and the level of significance is 5%. Data were analyzed using panel data regression methods and processed with Ms. Excel and EViews version 9 program. Statistical test showed that simultaneously SIZE, ROA, DAR, INST, and QA have significant effect on tax avoidance. ROA is the most dominant variable affect tax avoidance. Partially, SIZE and ROA has significant positively effect on tax avoidance. QA partially has significant negatively effect on tax avoidance. Meanwhile, DAR and INST showed no effect on tax avoidance. The results of this study indicate that, all independent variables can explain the variance in the dependent variable 44,72% based on determination coefficient test (R2).